On Reverses of Some Inequalities in n-Inner Product Spaces - Renu Chugh; Sushma Lather (International Journal of Mathematics and Mathematical Sciences)
We present some new reverses of Cauchy-Bunyakovsky-Schwarz inequality, and Triangle and Boas-Bellman Type inequalities in n-inner product spaces. The results obtained generalize the results of Dragomir (2003–2005) in n-inner product spaces. Also we provide some applications for determinantal integral inequalities.